Stability Studies of New Caged bis‐deoxy‐coelenterazine Derivatives and Their Potential Use as Cellular pH Probes. (11th November 2020) - Giuliani, Germano; Merolla, Assunta; Paolino, Marco; Reale, Annalisa; Saletti, Mario; Blancafort, Lluís; Cappelli, Andrea; Benfenati, Fabio; Cesca, Fabrizia
Abstract: The synthesis of new bis‐deoxy‐coelenterazine (1 ) derivatives bearing ester protective groups (acetate, propionate and butyrate esters) was accomplished. Moreover, their hydrolytic stability at room temperature was evaluated in dimethylsulfoxide (DMSO) as solvent, using the nuclear magnetic resonance (NMR) spectra of the key products at different time intervals. The results showed an increasing hydrolysis rate according to longest aliphatic chain, with a half‐life of 24 days of the more stable acetate derivative (4a ). Furthermore, the analysis of the experimental data revealed the greater stability of the enol tautomer in this aprotic polar solvent. This result was confirmed by theoretical calculations using the density functional theory (DFT) approach, which gave us the opportunity to propose a detailed decomposition mechanism. Additionally, the derivatives obtained were tested by bioluminescence luciferase assays to evaluate their potential use as extracellular pH‐sensitive reporter substrates of luciferase. The biological data support the idea that further structural modifications of these molecules may open promising perspectives in this field of research. Abstract : Studies on new caged coelenterazine reveal appreciable pH sensitivity, related to their hydrolysis kinetics.